EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN THINK TALK WRITE (TTW) PADA MATERI FUNGSI DITINJAU DARI ADVERSITY QUOTIENT SISWA KELAS VIII SMP NEGERI SE-KABUPATEN BOYOLALI TAHUN PELAJARAN 2015/2016 - Ulfa, Nur Fitriyana; Kusmayadi, Tri Atmojo; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this study was to know the effect of the learning models on the learning achievement in mathematics viewed from the students adversity quotient. The learning models compared were the cooperative learning of TAI, TTW, and direct learning model. The type of research was a quasi-experimental research with a 3x3 factorial design. The study population was all grade eighth students of Junior High Schools in Boyolali Regency in the academic year of 2015/2016. Instruments used for data collection were mathematics achievement test and adversity quotient questionnaire. The data analysis technique used was the two-way ANAVA with unbalanced cell. Based on the hypothesis test, it was concluded as follows. 1) The mathematics learning achievement of TAI was better than TTW and direct learning model, the mathematics learning achievement of TTW was better than direct learning model. 2) The mathematics learning achievement of students with climbers category was better than students with campers and quitters category; the mathematics learning achievement of students with campers category was better than students with quitters category. 3) Students with climbers category who were treated by TAI, TTW, and direct learning models had same mathematics learning achievement; the mathematics achievement of students with campers category who were treated by TAI was same of TTW and was better than direct learning model, students who were treated by TTW was better than direct learning model; students with quitters category who were treated by TAI had better mathematics learning achievement than students with TTW and direct learning model, students with TTW was same students with direct learning model. 4) In TAI, the mathematics learning achievement of students with climbers category was better than students with campers and quitters category, students with campers category was same students with quitters category; in TTW, the mathematics learning achievement of students with climbers category was same students with campers category and was better than students with quitters category, students with campers category was better than students with quitters category; in direct learning model, the mathematics learning achievement of students with climbers category was better than students with campers and quitters category, students with campers category was same students with quitters category.Key words: TAI, TTW, Direct Learning Model, Adversity Quotient, Mathematics Learning Achievement